2009
DOI: 10.1111/j.1442-2042.2009.02254.x
|View full text |Cite
|
Sign up to set email alerts
|

External validation and head‐to‐head comparison of Japanese and Western prostate biopsy nomograms using Japanese data sets

Abstract: The objective of this study was to perform external validation of a previously developed prostate biopsy nomogram (the CHIBA nomogram) and to compare it with previously published nomograms developed in Japanese and overseas populations. Two different cohorts of patients were used: one from the Chiba Cancer Center (n = 392) in which transperineal 16-core biopsy was performed, and another from Chibaken Saiseikai Narashino Hospital (n = 269) in which transrectal 16-core biopsy was carried out. All patients were J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…This approach is insensitive to systematic errors in calibration, an issue that has recently been reviewed (27 ); therefore, AUC comparisons alone are not appropriate for the validation of risk calculators. ROC curve analysis has been criticized when it is used as the only tool to differentiate between 2 cohorts (28,29 ), and results can be misinterpreted (18 ). Our results, however, confirm reviewed data (8,22 ) that show a general advantage of %fPSA-based multivariate models for PCa detection.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This approach is insensitive to systematic errors in calibration, an issue that has recently been reviewed (27 ); therefore, AUC comparisons alone are not appropriate for the validation of risk calculators. ROC curve analysis has been criticized when it is used as the only tool to differentiate between 2 cohorts (28,29 ), and results can be misinterpreted (18 ). Our results, however, confirm reviewed data (8,22 ) that show a general advantage of %fPSA-based multivariate models for PCa detection.…”
Section: Discussionsupporting
confidence: 81%
“…All of these tools use the PSA value as a decisive variable for risk stratification, in addition to such other variables as a suspicious DRE result and prostate volume. External validations of various nomograms have most often been performed by applying the nomograms to different populations (16,18 ). Table 1 shows that the different results obtained with the different PSA assays greatly affect the reliability of PCa risk prediction with nomograms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of GS upgrading in low-risk patients was significantly higher in TUSMC than in CSNH (92.3% in TUSMC versus 39.3% in CSNH, P < 0.01). Although external validation was often performed using combined datasets (16)(17)(18), using just the combined datasets might cause clinicians to miss a real tendency in each institution. Thus, this suggested that clinicians should construct a calibration plot and see the tendency for each institution, when a nomogram is applied to their patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…The two nomograms were externally validated in these two cohorts. To validate each nomogram externally, the area under the curve (AUC) values derived from receiver operating characteristic curves were estimated to calculate an unbiased measure of the ability of each nomogram to discriminate among patients, as described previously (16)(17)(18). The 95% confidence interval (95% CI) of the AUC values was calculated by bootstrapping.…”
Section: Discussionmentioning
confidence: 99%